1990
DOI: 10.1111/j.1476-5381.1990.tb14701.x
|View full text |Cite
|
Sign up to set email alerts
|

The action of atriopeptin III on renal function in two models of chronic renal failure in the rat

Abstract: 1 The natriuretic and diuretic effects of atriopeptin III (125, 250 and 500 ng kg 1, i.v.) were studied in groups of rats anaesthetized with pentobarbitone which were either sham controls, unilaterally nephrectomized controls, adenine-fed or subtotal nephrectomy chronic renal failure models. 2 Atriopeptin III given at these doses to the sham control animals had no effect on blood pressure, renal blood flow or glomerular filtration rate but reversibly increased urine flow, between 46% to 54%, absolute sodium e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1991
1991
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…However, Milman and colleagues recently provided evidence of blunted perfusion and renal vascular reactivity in anaesthetised mice with adenine‐induced CKD, using a magnetic resonance imaging technique for assessing the renal vascular response to hyperoxia . Consistent with these observations, renal blood flow measured directly by transit‐time ultrasound flowmetry or electromagnetic flowmetry under anaesthesia, and by the clearance of para‐aminohippurate in the conscious state, has been observed to be less in rats with adenine‐induced CKD compared to control animals. Thus, it is likely that abnormalities in both renal vascular structure and function contribute to the development of tissue hypoxia in adenine‐treated rats.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…However, Milman and colleagues recently provided evidence of blunted perfusion and renal vascular reactivity in anaesthetised mice with adenine‐induced CKD, using a magnetic resonance imaging technique for assessing the renal vascular response to hyperoxia . Consistent with these observations, renal blood flow measured directly by transit‐time ultrasound flowmetry or electromagnetic flowmetry under anaesthesia, and by the clearance of para‐aminohippurate in the conscious state, has been observed to be less in rats with adenine‐induced CKD compared to control animals. Thus, it is likely that abnormalities in both renal vascular structure and function contribute to the development of tissue hypoxia in adenine‐treated rats.…”
Section: Discussionmentioning
confidence: 88%
“…vations, renal blood flow measured directly by transit-time ultrasound flowmetry33 or electromagnetic flowmetry34 under anaesthesia, and by the clearance of para-aminohippurate in the conscious state,35 has been observed to be less in rats with adenine-induced CKD compared to control animals. Thus, it is likely that abnormalities in both renal vascular structure and function contribute to the development of tissue hypoxia in adenine-treated rats.…”
mentioning
confidence: 99%
“…The model of ACRF has mainly been used to examine the effects of severe renal failure on mineral and bone metabolism and extraosseous calcifications (14,23,24,(27)(28)(29). Only a limited number of studies have investigated kidney function and renal hemodynamics in detail in this model (13,19). The model of ACRF may show a higher resemblance to the clinical situation in CRF patients compared with the remnant kidney model, as rats typically develop more pronounced reductions in GFR (30,31).…”
mentioning
confidence: 99%
“…Thus, renal ischemia is the major factor driving the deficit in renal DO 2 in the early stages of Ad-CKD. Previous studies have demonstrated deficits in RBF (24,49) and anemia (47) in Ad-CKD when rats were treated with adenine for longer periods (i.e., 2 wk or more). However, to our knowledge, our present observations represent the first available quantification of renal DO 2 and V ˙O2 in Ad-CKD.…”
Section: Discussionmentioning
confidence: 97%